2004
DOI: 10.1086/383047
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sequence‐Based Identification of Gonococcal Transmission Clusters in a Large Metropolitan Area

Abstract: In large metropolitan areas, which typically have the highest rates of gonorrhea, the identification of chains of transmission by use of partner notification is problematic, and there is an increasing interest in applying molecular approaches, which would require new discriminatory high-throughput procedures for recognizing clusters of indistinguishable gonococci, procedures that identify local chains of transmission. Sequencing of internal fragments of 2 highly polymorphic loci, from 436 isolates recovered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
343
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(358 citation statements)
references
References 25 publications
9
343
0
6
Order By: Relevance
“…To further characterise the isolates of this study, N. gonorrhoeae multi-antigen sequence typing (NG-MAST) was performed as described earlier by Martin et al (2004). Briefly, internal fragments of the por (737 bp) and tbpB (553 bp) genes were PCR-amplified and sequenced in both directions as described for gyrA and parC genes.…”
mentioning
confidence: 99%
“…To further characterise the isolates of this study, N. gonorrhoeae multi-antigen sequence typing (NG-MAST) was performed as described earlier by Martin et al (2004). Briefly, internal fragments of the por (737 bp) and tbpB (553 bp) genes were PCR-amplified and sequenced in both directions as described for gyrA and parC genes.…”
mentioning
confidence: 99%
“…Mutations in the A subunit of DNA gyrase and ParC subunit of topoisomerase IV which confer resistance to ciprofloxacin were present whereby GyrA possessed the double mutations of Asp-95-to-Ala and Ser-91-to-Phe whilst an Asp-86-Asn mutation was found in ParC [15]. Multilocus sequence typing [16] and N. gonorrhoeae multi-antigen sequence typing [17] revealed that the isolate belonged to ST1587 and ST2575, respectively. To the best of our knowledge, both allelic profiles have not been reported for gonococcal isolates to date.…”
Section: New Cases Of Sexually Transmitted Infection Caused Bymentioning
confidence: 99%
“…Одним из известных и признанных методов мо-лекулярного типирования N. gonorrhoeae является метод NG-MAST-типирования (Neisseria gonorrhoeae-multi-antigen-sequence-typing), основанный на секвенировании фрагментов двух генов N. gonorrhoeae -porB гена, кодирующего белок поринового канала, и tbpB гена, кодирующего трансферрин-свя-зывающий белок [95]. В результате применения ме-тода каждому штамму гонококка присваивается свой индивидуальный номер -сиквенс-тип, кото-рый является уникальной характеристикой штамма.…”
Section: современные подходы к эпидемиологическому наблюдению над расunclassified
“…-об использовании метода NG-MAST для по-лучения генетической характеристики штаммов, ре-зистентных к антимикробным препаратам [103][104][105][106].…”
Section: современные подходы к эпидемиологическому наблюдению над расunclassified